2015
DOI: 10.1016/j.celrep.2014.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Intron Sequences Reveals Hallmarks of Circular RNA Biogenesis in Animals

Abstract: Circular RNAs (circRNAs) are a large class of animal RNAs. To investigate possible circRNA functions, it is important to understand circRNA biogenesis. Besides human ALU repeats, sequence features that promote exon circularization are largely unknown. We experimentally identified circRNAs in C. elegans. Reverse complementary sequences between introns bracketing circRNAs were significantly enriched in comparison to linear controls. By scoring the presence of reverse complementary sequences in human introns, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

27
916
3
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 925 publications
(947 citation statements)
references
References 27 publications
27
916
3
1
Order By: Relevance
“…Recently, circRNAs were rediscovered and shown to be the products of thousands of loci in eukaryotes, from fly and worm to mouse and human (Jeck et al 2013;Memczak et al 2013;Salzman et al 2013;Guo et al 2014;Westholm et al 2014;Zhang et al 2014;Ivanov et al 2015). Recent research into circRNA biogenesis has shown that backsplicing is catalyzed, though inefficiently (Zhang et al 2016), by the canonical spliceosomal machinery (Ashwal-Fluss et al 2014;Starke et al 2015;Wang and Wang 2015) and modulated by both cis-elements and trans-factors (Ashwal-Fluss et al 2014;Zhang et al 2014;Conn et al 2015;Ivanov et al 2015;Starke et al 2015; for review, see Chen and Yang 2015;Chen 2016). Different from the canonical splicing that joins an upstream 5 ′ splice (donor) site with a downstream 3 ′ splice (acceptor) site in a sequential order to produce a linear RNA, back-splicing occurs in a reversed orientation that links a downstream 5 ′ splice (donor) site to an upstream 3 ′ splice (acceptor) site to yield a circRNA.…”
mentioning
confidence: 99%
“…Recently, circRNAs were rediscovered and shown to be the products of thousands of loci in eukaryotes, from fly and worm to mouse and human (Jeck et al 2013;Memczak et al 2013;Salzman et al 2013;Guo et al 2014;Westholm et al 2014;Zhang et al 2014;Ivanov et al 2015). Recent research into circRNA biogenesis has shown that backsplicing is catalyzed, though inefficiently (Zhang et al 2016), by the canonical spliceosomal machinery (Ashwal-Fluss et al 2014;Starke et al 2015;Wang and Wang 2015) and modulated by both cis-elements and trans-factors (Ashwal-Fluss et al 2014;Zhang et al 2014;Conn et al 2015;Ivanov et al 2015;Starke et al 2015; for review, see Chen and Yang 2015;Chen 2016). Different from the canonical splicing that joins an upstream 5 ′ splice (donor) site with a downstream 3 ′ splice (acceptor) site in a sequential order to produce a linear RNA, back-splicing occurs in a reversed orientation that links a downstream 5 ′ splice (donor) site to an upstream 3 ′ splice (acceptor) site to yield a circRNA.…”
mentioning
confidence: 99%
“…65 Nevertheless, (CA) n simple repeats that are complementary over a <30-nt region appear to be sufficient to drive Drosophila Semaphorin-2b circular RNA biogenesis. 37 These data, as well as genomewide analyses 14,40,62,68 and detailed studies on the human EPHB4, 65 GCN1L1, 40,65 HIPK3, 65 LPAR1, 69 and POLR2A 40 circular RNAs, confirm the original Sry circular RNA biogenesis model 48 ( Fig. 2A) and suggest that it is applicable to thousands of eukaryotic genes.…”
Section: Introductionmentioning
confidence: 50%
“…Indeed, one can accurately predict many circular RNAs, especially from highly transcribed genes, by searching for pairs of complementary sequences in the flanking introns. 68 However, the presence of inverted intronic repeats is not sufficient for exon circularization. This is, in part, because of the co-transcriptional nature of splicing, but also because introns commonly contain many repetitive elements that compete for base pairing (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations